Prevalence, antibiotic sensitivity profile, and phylogenetic analysis of Escherichia coli isolated from raw dromedary camel milk in Matrouh Governorate, Egypt (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: Most people in Matrouh Governorate consume camel milk as a treatment for many diseases in a raw state to obtain nutritive value. Raw dromedary camel milk can be contaminated by Escherichia coli through fecal matter at any point of milk handling; therefore, it may lose its value and safety specifications. This survey aimed to estimate the incidence of E. coli in fresh camel milk. Materials and Methods: 100 fresh camel milk samples (50 from markets and 50 from farms) were randomly collected from different districts in Matrouh Governorate, Egypt, over 4 months for the detection of E. coli incidence through conventional bacterial isolation, molecular investigation, and gene sequencing. Results: The prevalence rates of E. coli in the examined market and farm raw camel milk based on conventional methods were 24% and 8%, respectively, while those by molecular identification using phoA as an E. coli determinate gene were 4% and 6%, respectively. Moreover, E. coli phoA gene phylogenetic analysis revealed high sequence similarity to E. coli strain CP033158.1 in India and E. coli strain CP047594.1 in China. Antibiotic sensitivity of E. coli isolates showed high susceptibility to norfloxacin (10 µg) and cefoperazone (75 µg). On the other hand, high resistance was found in rifamycin (30 µg) and cefoxitin (30 µg). Conclusion: The results indicate that market camel milk is more contaminated than the farms’ own. Additionally, antibiotic resistance is increasing due to antibiotic abuse.J. Adv. Vet. Anim. Res., 9(1): 138–143, March 2022http://doi.org/10.5455/javar.2022.i578